Ambon City Portrait of Flood Vulnerabilities: Spatial Analysis and Identification of Causing Factors (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Ambon City is one of the cities with a relatively high flood disaster intensity. This study aims to analyze the factors that cause flooding and determine the vulnerability of flooding. The method is based on a geographic information system (GIS) by integrating secondary and primary data. Parameters analyzed include elevation, rainfall, slope, soil type, and land use. Study results show that the factors causing flooding in Ambon City include relatively high-intensity rains, land use patterns dominated by mixed gardens, slopes in lowland areas, low elevations, and soil types easily inundated with water. The flood hazard zone is divided into three classes, namely high, medium, and low hazard zones. Areas with high vulnerability are 2,251.3 ha (6.99%) of the total area of the study area. For this reason, the community and the Ambon City government need to pay attention to this area in dealing with flood disasters.